Immediate Point-of-Care Testing of Breastmilk Sodium and Potassium Concentrations in Women with Mastitis - Emma L. Heron; Ching Tat Lai; Leanda J. McKenna; Adelle M. McArdle; Donna T. Geddes (Proceedings, 2023)
Sodium (Na) and potassium (K) concentrations in breastmilk are often used as biomarkers to define mastitis in lactating women and can be measured with small portable point-of-care ion-selective electrodes (ISEs). The aim of this study was to test the ISEs at the point of care for accuracy and acceptability in women with mastitis. Up to 5 mL of expressed breastmilk from the affected breast of 43 women with mastitis was collected at three timepoints (day 1, 3, and 10). Immediate Na and K ISE testing was later compared to the laboratory measure of inductively coupled plasma–op-tical emission spectrometry (ICP-OES). The results revealed a statistically significant difference in Na and K concentrations between the point-of-care and laboratory testing (both p = 0.001, Wilcoxon signed-rank test); however, the difference was not statistically significant when compared for Na:K ratio (p = 0.49, Wilcoxon signed-rank test). The Bland–Altman limits of agreement were acceptable, with the majority of measurements lying within two standard deviations of the mean (Na: 94%; K: 95%; and Na:K: 96%). The testing techniques were significantly correlated for Na (R2 = 0.79, p = 0.001) and Na:K (R2 = 0.99, p = 0.001). Overall, participants rated the ISE point-of-care testing as very acceptable. In conclusion, immediate ISE point-of-care testing for breastmilk Na:K ratio in women with mastitis is clinically accurate and acceptable.